Proton reirradiation for recurrent or new primary breast cancer in the setting of prior breast irradiation. (December 2021) - Choi, J. Isabelle; Khan, Atif J.; Powell, Simon N.; McCormick, Beryl; Lozano, Alicia J.; Del Rosario, Gabriely; Mamary, Jacqueline; Liu, Haoyang; Fox, Pamela; Gillespie, Erin; Braunstein, Lior Z.; Mah, Dennis; et al.
Highlights: Proton therapy is a viable salvage treatment in the setting of prior breast radiation. Proton reirradiation provides excellent locoregional tumor control for breast cancer. Breast or chest wall reirradiation toxicity may rarely require surgical intervention. Abstract: Background and purpose: Late local recurrences and second primary breast cancers are increasingly common. Proton beam therapy (PBT) reirradiation (reRT) may allow safer delivery of a second definitive radiotherapy (RT) course. We analyzed outcomes of patients with recurrent or new primary breast cancer who underwent reRT. Materials and methods: In an IRB-approved retrospective study, patient/tumor characteristics, treatment parameters, outcomes, and toxicities were collected for all consecutive patients with recurrent or new primary non-metastatic breast cancer previously treated with breast or chest wall RT who underwent PBT reRT. Results: Forty-six patients received reRT using uniform (70%) or pencil beam (30%) scanning PBT. Median first RT, reRT, and cumulative doses were 60 Gy (range 45–66 Gy), 50.4 Gy(RBE) (40–66.6 Gy(RBE)), and 110 Gy(RBE) (96.6–169.4 Gy(RBE)), respectively. Median follow-up was 21 months. There were no local or regional recurrences; 17% developed distant recurrence. Two-year DMFS and OS were 92.0% and 93.6%, respectively. Nine of 13 (69.2%) patients who underwent implant or flap reconstruction developed capsular contracture, 3 (23.1%) requiring surgical intervention. One (7.7%) patient developed grade 3 breast pain requiring mastectomy after breast conserving surgery. No acute or late grade 4–5 toxicities were seen. Increased body mass index (BMI) was protective of grade ≥ 2 acute toxicity (OR = 0.84, 95%CI = 0.70–1.00). Conclusion: In the largest series to date of PBT reRT for breast cancer recurrence or new primary after prior definitive breast or chest wall RT, excellent locoregional control and few high-grade toxicities were encountered. PBT reRT may provide a relatively safe and highly effective salvage option. Additional patients and follow-up are needed to correlate composite normal tissue doses with toxicities and assess long-term outcomes.